Dominica : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1997)
This paper describes economic developments in Dominica during the 1990s. The paper highlights that despite the low overall growth rates observed in 1991-95, output in service-related industries grew rapidly. The hotels and restaurants sector expanded at a yearly average rate of 7.5 percent in 1991-95, while Dominica's tourism receipts increased at an average annual rate of about 9 percent. Tourism expansion also stimulated transportation services, and value added in the transportation sector grew on average by 4 1\2 percent annually.